Borderland Mystery and Tibetan Writing: On Ma Yuans Non-linear Spatial Narrative Strategy in Tibetan Novels; [Misterio de la Frontera y Escritura Tibetana: Sobre la Estrategia Narrativa Espacial No Lineal de Ma Yuan en Novelas Tibetanas] - Lim Chsing Chsing (Tanjung Malim, 2024)
Borderland Mystery and Tibetan Writing: On Ma Yuans Non-linear Spatial Narrative Strategy in Tibetan Novels; [Misterio de la Frontera y Escritura Tibetana: Sobre la Estrategia Narrativa Espacial No Lineal de Ma Yuan en Novelas Tibetanas] by Lim Chsing Chsing